Secretin Modulates the Postnatal Development of Mouse Cerebellar Cortex Via PKA- and ERK-dependent Pathways - Wang, Lei; Zhang, Li; Chow, Billy K. C. (Frontiers in Cellular Neuroscience, 2017)
Postnatal development of the cerebellum is critical for its intact function such as motor coordination and has been implicated in the pathogenesis of psychiatric disorders. We previously reported that deprivation of secretin from cerebellar Purkinje neurons impaired motor coordination and motor learning function, while leaving the potential role of secretin in cerebellar development to be determined. Secretin and its receptor were constitutively expressed in the postnatal cerebellum in a temporal and cell-specific manner. Using a secretin knockout mouse model, we provided direct evidence showing altered developmental patterns of Purkinje cells and granular cells. Secretin deprivation reduced the Purkinje cell density, impaired the Purkinje cell dendritic formation, induced accelerated granular cell migration, and potentiated cerebellar apoptosis. Furthermore, our results indicated the involvement of protein kinase A (PKA) and extracellular signal regulated kinase (ERK) signaling pathways in secretin-mediated protective effects against neuronal apoptosis. Results of this study illustrated a novel function of secretin in the postnatal development of cerebellum, emphasizing the necessary role of secretin in cerebellar-related functions.